Estudio de la influencia de la distancia de plantacion en la produccion de papa - Hernandez, H.=700 1 Arzuaga, J.; Torres, W.
(Es, En)
Ilus., 7 ref.
Keywords: SOLANUM TUBEROSUM; ESPACIAMIENTO; PLANTACION; PRODUCCION; CUBA; CULTIVOS TROPICALES